A frame-analytical perspective on conflict between people and an expanding wolf Canis lupus population in central Italy. Issue 4 (October 2014) - Vitali, Chiara
Abstract Attempts to mitigate conflict between wolves and livestock breeding in the Mugello area of central Italy have so far proven to be costly, resource-intensive and fraught with tension. I applied frame analysis as a tool for investigating the roots of such tensions. The frame-analytical perspective highlighted that, while current policy focuses on improving technical approaches, conflict is also fuelled by a discrepancy in the frames of meaning that groups of stakeholders construct around the issue of wolf management. I outline two discordant frames: a dominant valuable wolf frame, currently underlying policy, and a political wolf frame that challenges existing management aims. Barriers to communication and potential points of mediation are identified. In addition, I outline a third, problematic wolf frame that may act as a potential aid in the process of bridging the two discordant frames, which is identified as a condition for successful wolf management.